Review Formulasi Emulsi Dalam Pengembangan Sediaan Farmasi - Hariyansyah, Marsela febrianti (Jurnal Farmasi Sains dan Teknologi, 2025)
Emulsions are thermodynamically unstable biphasic systems that require appropriate formulation strategies to maintain their stability. Synthetic surfactants are commonly used as stabilizers, but concerns regarding their toxicity and environmental impact have prompted the search for safer alternatives. One promising innovation is the use of solid particles in Pickering emulsions, which offer improved stability and enhanced safety. This article uses a literature review method, analyzing national and international journals published between 2015 and 2025, focusing on the formulation and physical evaluation of emulsions. The review findings indicate that the success of emulsion formulation depends on the type of active ingredient, choice of emulsifier, preparation method, and storage conditions. Various studies emphasize the importance of physical evaluations—such as organoleptic properties, pH, homogeneity, spreadability, adhesiveness, and viscosity—in determining emulsion quality. The use of natural ingredients and alternative emulsifiers has shown potential in enhancing the stability and safety of topical emulsions. In conclusion, the development of stable and effective emulsions requires a comprehensive understanding of the physical characteristics of components and a thorough evaluation of the formulations. Pickering emulsions present an innovative approach that deserves further exploration in pharmaceutical preparations.